Investigating the experience of local community networks of disaster self-management: A qualitative study in Thailand - Khanitta Nuntaboot; Peerapong Boonsawasdgulchai; Nisachon Bubpa; Marie T Benner (Wolters Kluwer Medknow Publications, 2020)
Background: Thailand is exposed to multiple climate-related hazards. Those cause disaster, instability and destruction to human life and property. People affected by disasters need self-help capabilities. Therefore, local administration organizations (LAOs) and local community networks are critical. They act as social capital in communities who can contribute meaningfully to disaster management systems. Objective: The study aimed to assess procedures and activities of community networks focusing on disaster management and how social capitals are utilized. Methods: The qualitative study was conducted with 65 informants recruited through purposive sampling and snowball techniques from six outstanding LAOs. We analyzed data from in-depth interviews, observations, and focus group discussions with key informants. An inductive thematic analysis was performed to identify themes on procedures and activities related to social capital. Content analysis was used to analyze the data. Results: We identified three main outcomes. The social capital involved and collaborated with LAOs included civil groups, community organizations, community leaders, and other public and private organizations. Procedures and activities related to social capital working in disaster management in communities included predisaster phase, disaster phase, and postdisaster and recovery phase. The overall local community network was key to help disaster affected people in communities effectively. Conclusion: The findings suggest that social capital participation builds up a sustainable community self-management. The potential enhancement of the local community self-management is strongly based on relationships within the community structure. Community disaster self-management and is likely reducing risk factors and mitigate vulnerability.